A holistic approach to individual-level innovation implementation. Issue 4 (2nd October 2019) - Pak, Jongwook; Li, Longzhen; Chung, Goo Hyeok
ABSTRACT: Innovation and information systems scholars have extensively studied the individual-level innovation implementation process, drawing on the theories of technology acceptance (e.g., TAM2). However, based on the less-balanced theoretical underpinnings, they have constituted antecedents of implementation: some included either individual or organisational factors; others merely viewed individual characteristics as contingencies while emphasising organisational factors as predictors. In this study, we present a more balanced view, by considering dispositional, experiential and organisational readiness to innovation implementation as three antecedents that predict components of the TAM2 (i.e., perceived usefulness, perceived ease of use and subjective norm). Conceptualising three antecedents as personal innovativeness, innovation self-efficacy and facilitating climate, respectively, we examine the relationships between readiness factors and the TAM2, subsequently influencing innovation implementation and its outcomes. Our results confirmed that personal innovativeness and facilitating climate were positively related to perceived usefulness, perceived ease of use, and subjective norm but that innovation self-efficacy was positively associated with only the first two factors. Among the three antecedents in our sample, facilitating climate most strongly predicted the three components of the TAM2. Furthermore, perceived usefulness and perceived ease of use predicted intention to use, which in turn led to implementation behaviour and extended innovation effectiveness.